Efforts to improve self-management using Google Calendar - Tri Na'imah; Feri Wibowo; Retno Dwiyanti (Universitas Muhammadiyah Magelang, 2022)
In 'Aisyiyah organizations, women play a variety of roles, including workers, organizational activists, and housewives. As a result, a woman should be able to manage her time so that she can take care of her family, her job, and the 'Aisyiyah organization. This program aims to increase knowledge about self-management and improve skills using the Google Calendar application for the head of the 'Aisyiyah branch (PRA) of Darul Muhajirin Sumampir, North Purwokerto. The method used in this program is education and training. The outcome reveals an improvement in post-test scores following self-management training. The improvement in skills can be seen from the success of participants in using the Google Calendar application to schedule daily activities.